2013
DOI: 10.1039/c2ob26966j
|View full text |Cite
|
Sign up to set email alerts
|

Benzimidazolium-based synthetic chloride and calcium transporters in bacterial membranes

Abstract: Herein, we present the first example of a benzimidazolium-based artificial transmembrane chloride transporter and a synthetic calcium ionophore that can regulate intracellular calcium concentrations in bacteria.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
31
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(33 citation statements)
references
References 45 publications
1
31
0
Order By: Relevance
“…Phenylethynylbenzyl (PEB) -disubstituted imidazolium and benzimidazolium were shown to self-assemble inside phospholipid membranes and form stable channels through π-π interactions (Figure 1A) 13 . The transport of protons and ions through these open channels induced membrane perturbation, depolarization and bacterial death.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Phenylethynylbenzyl (PEB) -disubstituted imidazolium and benzimidazolium were shown to self-assemble inside phospholipid membranes and form stable channels through π-π interactions (Figure 1A) 13 . The transport of protons and ions through these open channels induced membrane perturbation, depolarization and bacterial death.…”
Section: Resultsmentioning
confidence: 99%
“…The transport of protons and ions through these open channels induced membrane perturbation, depolarization and bacterial death. Even if the PEB -disubstituted benzimidazolium salts were very active on bacterial membranes, their potential as mitochondrial membrane perturbators was not further explored because of their high toxicity on red blood cells (HC 50 at 0.15 mM) [13][14] . The replacement of one PEB unit with a phenyl or a methyl group resulted in less toxic compounds (HC 50 at 1 mM for the benzyl and 150 mM for the methyl substituent), forming more compact aggregates in the membranes.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[11,12] Previous studies by our group have shown that the addition of two phenylethynylbenzyl (PEB) arms to ab enzimidazolium cation (Figure1)r esulted in the formation of self-assembled channels in the phospholipid membranes. [13] We previously showedt hat bis-benzimidazolium salts 3a-c have the ability of inducing electrolytici mbalance andd isrupting the integrity and potential of planktonic bacterial membranes. [14] Herein, we were interested to see how the replacement of the PEB arm The increased prevalence of antibiotic-resistantb acteria is a critical issue for human health.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies by our group have shown that the addition of two phenylethynylbenzyl (PEB) arms to a benzimidazolium cation (Figure ) resulted in the formation of self‐assembled channels in the phospholipid membranes . We previously showed that bis‐benzimidazolium salts 3 a – c have the ability of inducing electrolytic imbalance and disrupting the integrity and potential of planktonic bacterial membranes .…”
Section: Introductionmentioning
confidence: 99%